2021
DOI: 10.21037/atm-21-392
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the diagnostic value of intravenous/ peritumoral injection of indocyanine green for metastatic lymph node location in patients with head and neck squamous cell carcinoma (HNSCC)

Abstract: Background: Accurate assessment of regional lymph node (LN) status is essential for the treatment of head and neck squamous cell carcinoma (HNSCC) patients. In this study, we aimed to compare the difference between intravenous injection of indocyanine green (ICG) and peritumoral injection of ICG in the location of metastatic LNs.Methods: Twenty-nine patients were enrolled in this study with 13 patients receiving intravenous injection of ICG and 16 patients receiving peritumoral injection of ICG. During the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recently, surgery has gained in popularity, exempli ed by Xia et al [7] who reported a sensitivity of 98.1% and speci city of 89.1% in the detection of metastatic nodes. In addition, a recent study [8] demonstrated the ability of ICG to identi ed neck metastases in a population of young adults and children with a sensitivity of 83%, a speci city of 88%, a positive predictive value (PPV) of 91%, and a negative predictive value (NPV) of 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, surgery has gained in popularity, exempli ed by Xia et al [7] who reported a sensitivity of 98.1% and speci city of 89.1% in the detection of metastatic nodes. In addition, a recent study [8] demonstrated the ability of ICG to identi ed neck metastases in a population of young adults and children with a sensitivity of 83%, a speci city of 88%, a positive predictive value (PPV) of 91%, and a negative predictive value (NPV) of 86%.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of fluorescence signal in the lymph nodes after ALND, they proposed two hypotheses to explain ICG staining: fluorescent dye accumulation through the metastatic tumor tissues of the involved lymph nodes and dye loading in non-metastatic lymph nodes when in an inflammatory state [ 8 ]. Xia et al and Digonnet et al also measured the fluorescence signal intensity in SLN or cervical lymphadenectomy after intravenous or peritumoral ICG injection in head and neck cancer studies [ 9 , 35 ]. They reported a higher fluorescence signal in metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration mainly focuses on the diagnosis or treatment of tumor LNs metastasis [ 51 , 52 ]. For example, Xia [ 53 ] et al demonstrated the intravenous mode of indocyanine green (ICG) administration has a higher diagnostic value for localization of metastatic LNs than peritumoral injection in clinical samples of head and neck squamous cell carcinoma (HNSCC).…”
Section: Administration Routes Towards Lnsmentioning
confidence: 99%